2014
DOI: 10.5535/arm.2014.38.1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Determination of Treatment Success and Emotional Factors in Patients With Chronic Musculoskeletal Pain

Abstract: ObjectiveTo investigate the relationship of the patient's criteria of successful treatment to emotional factors in patients with chronic musculoskeletal pain.MethodsPatients who visited our outpatient hospital due to chronic musculoskeletal pain were evaluated using a questionnaire survey. Patients were evaluated with the Patient-Centered Outcomes Questionnaire (PCOQ) to investigate their expectation and criteria for success regarding treatment of chronic musculoskeletal pain. Beck Depression Inventory and Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Although perceptions of symptom importance have not been studied in cancer patients, these perceptions have been assessed in patients with chronic pain conditions (Robinson et al, 2005). Studies have found that not all patients prioritize improvement in the same symptoms; some patients were most interested in pain reduction, whereas others placed greater emphasis on improvement of other symptoms, such as fatigue or emotional distress (Robinson et al, 2005; Yi et al, 2014; Zeppieri et al, 2012). Not only do patients differ in the specific symptoms they consider most important, they also differ in the overall number of symptoms they prioritize for improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although perceptions of symptom importance have not been studied in cancer patients, these perceptions have been assessed in patients with chronic pain conditions (Robinson et al, 2005). Studies have found that not all patients prioritize improvement in the same symptoms; some patients were most interested in pain reduction, whereas others placed greater emphasis on improvement of other symptoms, such as fatigue or emotional distress (Robinson et al, 2005; Yi et al, 2014; Zeppieri et al, 2012). Not only do patients differ in the specific symptoms they consider most important, they also differ in the overall number of symptoms they prioritize for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences in number of prioritized symptoms may be related to important outcomes. For example, patients with chronic pain who rate all symptoms as highly important have been found to experience greater anxiety and depressive symptoms (Yi et al, 2014; Zeppieri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Table shows the characteristics of the included studies. In most quantitative studies (N=18), a self‐constructed questionnaire was used; six studies used a validated questionnaire . Most studies (N=12) were conducted in the USA, seven in Europe, two in Australia and two in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In most quantitative studies (N=18), a self-constructed questionnaire [25][26][27][28][29][30][31][32][33] was used; six studies used a validated questionnaire. [34][35][36][37][38][39] Most studies (N=12) were conducted in the USA, seven in Europe, two in Australia and two in Asia. Research aims and management settings were diverse.…”
Section: Data Collection Extraction and Synthesismentioning
confidence: 99%
“…Nearly a third of FM patients simply wanted to know if they actually believed that the disease with which they were diagnosed really existed. These desires took precedence over the development of more effective drugs, more funding for research and better diagnosis 18,24,43 . Patients are more satisfied when their physicians adopt a therapeutic set, not limited to the prescribed drugs, and use a greater variety of methods to deal with FM symptoms, showing more concern with them.…”
Section: Fibromyalgia Patients' Needs Under Their Own Perspectivesmentioning
confidence: 99%